Employing the elements of film construction in embodying the style cinematically: عامر الحديثي (Al-Academy, 2016)
The researcher concluded that it consists of several types of structures, where the intellectual structure related to the choice of the idea, its treatment, its effect, the choice of the topic, the way ideas are addressed and presented in the film, and then the dramatic structure of the film's characters, the formulation of its events, its dramatic composition, its temporal arrangement, the identification of the parties to the conflict and their management, then these are formulated. Visions and ideas through the visual and audio signal systems, which work to highlight the stylistic features in the character of the film director.